EXPLORING THE ROLE OF ETHICAL RELATIVISM, MENTAL ACCOUNTING, AND TAX DIGITALIZATION IN MSME TAX COMPLIANCE - Ahmad Danang Sagita; Elia Mustikasari (Universitas Airlangga, 2025)
This study aims to provide empirical evidence on the influence of ethical relativism, mental accounting, and tax digitalization on tax compliance among MSME taxpayers at KPP Pratama Banyuwangi. Using a quantitative approach, this research involves 120 individual MSME taxpayers selected through accidental sampling. Data were analyzed using multiple linear regression assisted by SPSS version 26. The results show that ethical relativism does not significantly affect tax compliance, as taxpayer decisions tend to be guided more by regulatory and rational considerations than by moral perspectives. In contrast, both mental accounting and tax digitalization have a positive and significant influence, indicating that effective financial categorization and accessible digital tax services enhance taxpayer compliance. These findings suggest that psychological and technological factors play a vital role in fostering tax compliance beyond ethical reasoning. The implication of this research highlights the importance for tax authorities to improve digital infrastructure and taxpayer financial literacy as strategic steps to increase compliance rates